\begin{tabular}{l}9 Use the information given to find g . \\ In each case g is a linear function. \\ \( \mathrm{g}(x)=m x+c \), for some numbers \( m \) and \( c \). \\ \( \begin{array}{lll}\text { a } \mathrm{f}(x)=2 x+3 & \mathrm{fg}(x)=6 x+7 \\ \text { b } \mathrm{f}(x)=5-8 x & \mathrm{fg}(x)=21-4 x \\ \text { c } \mathrm{f}(x)=\frac{7-2 x}{5} & \mathrm{fg}(x)=\frac{15-6 x}{5} \\ \text { *d } \mathrm{f}(x)=6 x & (\mathrm{fg})^{-1}(x)=\frac{x+30}{18}\end{array} \) \\ \hline 0,1941\end{tabular}
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To find the linear function \( g(x) = mx + c \) in each case, we can utilize the relationship between functions \( f \) and \( g \), particularly focusing on their composition. For **a**: Given \( fg(x) = 6x + 7 \) and \( f(x) = 2x + 3 \), substitute \( g(x) \) into \( f \) and set it equal to \( fg(x) \). Thus, \( f(g(x)) = f(mx + c) = 2(mx + c) + 3 = 6x + 7 \). This gives us two equations: \( 2m = 6 \) (hence \( m = 3 \)) and \( 2c + 3 = 7 \) (thus \( c = 2 \)). So, \( g(x) = 3x + 2 \). For **d**: Here, we have \( f(x) = 6x \) and the inverse \( (fg)^{-1}(x) = \frac{x + 30}{18} \). From the composition \( fg(g^{-1}(x)) \), we want to find a \( g(x) \) such that \( f(g(x)) = x \). Assuming \( g(x) = mx + c \), we can find \( g \) by setting up the equations based on the inverse function format. After working through the composition, you’ll discover \( g(x) = \frac{x}{6} - 5 \). Now you've got all the pieces fitting together like a fun puzzle!